Kasyf Asālīb Lughah al-Qur’ān al-Latī Tusaṭṭiru Ṭa‘na al-Ruhbān - Hasan Anshori (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2017)
Among the contemporary intellectual trends that claim to represent a reformist approach to religion, their proponents assert that they have conducted thorough and in-depth studies of Islam from various perspectives. They began examining the Qur’an and claimed that it contains linguistic errors. From this assumption, they concluded that the Qur’an is not infallible as Muslims believe, and even argued that it is not a sacred book due to the alleged errors within it. Before reaching these conclusions, however, these critics relied on books written by opponents of Islam, including a work entitled Is the Qur’an Infallible? This research aims to uncover the hidden linguistic aspects behind the Qur’anic verses that are alleged by them to contain grammatical errors, in order to refute the claims of those who criticize the Book of Allah from a linguistic perspective.